Respuesta :

Answer:

[tex]f(a+h)-f(a)=2ah+h^2+5h[/tex]

Step-by-step explanation:

Given function is [tex]f\left(x\right)=x^2+5x[/tex].

Using that function, we need to determine the value of f(a+h)-f(a).

[tex]f\left(x\right)=x^2+5x[/tex]

[tex]f\left(a+h\right)=(a+h)^2+5(a+h)[/tex]

[tex]f\left(a+h\right)=a^2+2ah+h^2+5a+5h[/tex]

similarly

[tex]f\left(a\right)=a^2+5a/tex]

Then [tex]f(a+h)-f(a)=(a^2+2ah+h^2+5a+5h)-(a^2+5a)[/tex]

[tex]f(a+h)-f(a)=a^2+2ah+h^2+5a+5h-a^2-5a[/tex]

[tex]f(a+h)-f(a)=2ah+h^2+5h[/tex]

Hence final answer is [tex]f(a+h)-f(a)=2ah+h^2+5h[/tex].

ACCESS MORE